Nonessential amino acid is not nonessential in geriatric patients: implications for maxillofacial wound healing and bone repair - Seong-Gon Kim (Maxillofacial Plastic and Reconstructive Surgery)
Abstract Background Nonessential amino acids (NEAAs) are traditionally regarded as dispensable because they can be synthesized endogenously from glucose-derived intermediates. Emerging evidence, however, shows that the capacity for de novo NEAA biosynthesis declines in aged tissues, rendering several of these molecules conditionally essential during periods of stress such as surgery or fracture repair. Main body In the cranio-maxillofacial arena — where bone and soft-tissue regeneration must occur in an environment already compromised by osteoporosis, multimorbidity, and restricted oral intake — insufficient NEAA supply may translate into delayed union, wound dehiscence, and heightened infection risk. This narrative review integrates biochemical, preclinical, and clinical data to map age-dependent changes in the serine/glycine, glutamine/glutamate, arginine/citrulline, cysteine/trans-sulfuration, and alanine cycles, examines their impact on osteogenesis and mucosal healing, and evaluates nutritional or pharmacological strategies to restore NEAA sufficiency. Particular attention is paid to serine-one-carbon metabolism, the intestinal-renal arginine axis, and redox-sensitive cysteine pathways, all of which are intimately linked to collagen deposition, osteoblast differentiation, and immune modulation. Conclusion We conclude that proactive optimization of NEAA status — through targeted supplementation or metabolic activation — represents a low-risk, biologically rational adjunct to enhance postoperative outcomes in geriatric maxillofacial patients.